2017
DOI: 10.1002/hed.24707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic percutaneous endoscopic gastrostomy tube on swallowing in advanced head and neck cancer: A randomized controlled study

Abstract: A prophylactic PEG tube can be used without an increased risk of long-term dysphagia in patients with head and neck cancer. © 2017 Wiley Periodicals, Inc. Head Neck 39: 908-915, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 24 publications
(68 reference statements)
1
52
3
Order By: Relevance
“…15 Study has shown that early percutaneous endoscopic gastrostomy (PEG) placement can increase the completeness rate of concurrent chemotherapy. 42 Although PEG catheterization is more receptive than nasogastric tubes, studies [43][44][45] have also shown that PEG may result in a decrease in swallowing process. [33][34][35][36][37] Studies have shown that prophylactic PEG can improve quality of life 38 and reduce the risk of aspiration, hospitalization, medical costs, 39 weight loss, length of stay, 40 and radiotherapy interruption rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Study has shown that early percutaneous endoscopic gastrostomy (PEG) placement can increase the completeness rate of concurrent chemotherapy. 42 Although PEG catheterization is more receptive than nasogastric tubes, studies [43][44][45] have also shown that PEG may result in a decrease in swallowing process. [33][34][35][36][37] Studies have shown that prophylactic PEG can improve quality of life 38 and reduce the risk of aspiration, hospitalization, medical costs, 39 weight loss, length of stay, 40 and radiotherapy interruption rate.…”
Section: Discussionmentioning
confidence: 99%
“…41 Prophylactic PEG was more common than reactive PEG in abroad, with rate of catheterization 51.75% and 13.5%, respectively. 42 Although PEG catheterization is more receptive than nasogastric tubes, studies [43][44][45] have also shown that PEG may result in a decrease in swallowing process. It was suggested that PEG may not be considered before the radiation dose reaches 30 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing question in our field as to whether prophylactic feeding tube placement may contribute to long‐term dysphagia. Past studies have had mixed results, with some showing better long‐term quality of life and shorter tube dependence without prophylactic gastrostomy tube placement and others refuting this . Unfortunately, we are unable to determine definitively from our data which gastrostomy tubes were placed prophylactically and which were placed reactively, therefore, we were unable to analyze the possible contribution of this risk factor.…”
Section: Discussionmentioning
confidence: 75%
“…However, these were either small in sample size or evaluated heterogenous patient cohorts . One of the major concerns is the potential risk of prolonged tube dependency and swallow musculature atrophy, however a recent prospective study from Sweden was able to show that patients with PEG tube do not have an increased risk in a long‐term follow up …”
Section: Discussionmentioning
confidence: 99%